Experimental and analytical assessment of the capacity of traditional single notch joints and impact of retrofitting by self-tapping screws - Sobra, Karel (2016)
The joints are the most crucial parts of a timber building and determine the overall structural behaviour, load-bearing capacity and failure mechanisms. Therefore, keeping the joints fully functional is of utmost importance to ensure a desired structural performance of timber buildings under various actions. Since replacement of damaged parts of an existing structure is expensive and in many cases very difficult to perform in situ, retrofitting to avoid failure becomes an increasingly widespread strategy. In this paper, the capacity and failure mechanisms of single notch joints before and after a simple retrofitting intervention by means of self-tapping screws were investigated. To this end, a series of tests were carried out during the 5th COST FP 1101 Training School, held in University of Minho, Portugal. The joints were first tested under compression, and the load-bearing capacity values obtained at the end of tests were compared to the capacity values calculated using theoretical models proposed in a variety of national codes. Then, tested joints were retrofitted using self-tapping screws. The retrofitting strategy aimed to prevent failure mechanism that was shown to dominate joints' behaviour in the unreinforced state, rather than to increase the load-bearing capacity or stiffness. The impact of retrofitting on the joints' performance was discussed and the success of the proposed intervention was further debated.